2020
DOI: 10.1167/jov.20.10.17
|View full text |Cite
|
Sign up to set email alerts
|

What do radiologists look for? Advances and limitations of perceptual learning in radiologic search

Abstract: Supported by guidance from training during residency programs, radiologists learn clinically relevant visual features by viewing thousands of medical images. Yet the precise visual features that expert radiologists use in their clinical practice remain unknown. Identifying such features would allow the development of perceptual learning training methods targeted to the optimization of radiology training and the reduction of medical error. Here we review attempts to bridge current gaps in understanding with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 113 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…For instance, expert chess players tend to have fewer, longer fixations in the middle, while novices scan more (Charness et al, 2001). Expert radiologists tend to fixate abnormalities earlier than novices (Nodine et al, 2002;Alexander et al, 2020). Even the ability to keep one's eye still is affected by training and experience (Cherici et al, 2012;Di Russo et al, 2003).…”
Section: Expertisementioning
confidence: 99%
“…For instance, expert chess players tend to have fewer, longer fixations in the middle, while novices scan more (Charness et al, 2001). Expert radiologists tend to fixate abnormalities earlier than novices (Nodine et al, 2002;Alexander et al, 2020). Even the ability to keep one's eye still is affected by training and experience (Cherici et al, 2012;Di Russo et al, 2003).…”
Section: Expertisementioning
confidence: 99%
“…However, while the contrast in these nodal regions was often visibly different in synthetic images, their relative size, shape, and texture may remain similar to the ground-truth image. It has been suggested that geometrical properties, i.e., size, shape, and texture, are often particularly important for image segmentation ( 58 , 59 ). Therefore, cases where tumor volume synthesis “fails” may not necessarily render these images clinically unusable, but additional research should be performed to verify these claims.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we recommend that referral clinicians look at their patients' studies rather than relying solely on the radiology report. While radiologists' perceptual abilities to detect abnormalities are more developed than those of referral clinicians (Reinus, 1995;Waite et al, 2019Waite et al, , 2020Alexander et al, 2020), a second viewer who is more attuned to the patient's history may notice details that the first viewer missed.…”
Section: Distinguishing Illusion From Realitymentioning
confidence: 99%